2021
DOI: 10.1063/5.0053498
|View full text |Cite
|
Sign up to set email alerts
|

Observation of planar Hall effect in topological insulator—Bi2Te3

Abstract: Planar Hall effect (PHE) in topological insulators (TIs) is discussed as an effect that stems mostly from conduction due to topologically protected surface states. Although surface states play a critical role and are of utmost importance in TIs, our present study in Bi 2 Te 3 thin films reflects the need for considering the bulk conduction in understanding the origin of PHE in TIs. This necessity emerges from our observation of an unconventional increase in the PHE signal with TI thickness and temperature wher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
1
17
1
Order By: Relevance
“…3 (e), which is different from the proposed anomalous PHR in two dimensional systems [35][36][37]. Outside region III, there is no significant ϕ dependence of R xx and R xy , conventional PHE signal of Bi 2 Te 3 is observed at high fields (B ≥ 1 T -see SI) [28].…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…3 (e), which is different from the proposed anomalous PHR in two dimensional systems [35][36][37]. Outside region III, there is no significant ϕ dependence of R xx and R xy , conventional PHE signal of Bi 2 Te 3 is observed at high fields (B ≥ 1 T -see SI) [28].…”
contrasting
confidence: 63%
“…Planar Hall effect (PHE) refers to the development of a transverse voltage in response to longitudinal current and an in-plane magnetic field B, such that the influence of Lorentz force is absent [27,28]. In a conventional ferromagnet or a TI, PHE depends on ϕ, the in-plane angle between current and magnetic field, as R xy ∝ sin 2ϕ and R xx ∝ cos 2 ϕ, where R xy is the planar Hall resistance (PHR) [10,29] and R xx is the planar magneto-resistance (PMR) [30].…”
mentioning
confidence: 99%
“…Hall effect [121], weak antilocalization [122,123] and Shubnikov-de Haas (SdH) oscillations [84,124] have been reported in magnetotransport experiments on Bi 2 Te 3 thin films. In addition, micro-and nano-structured Bi 2 Te 3 thin films demonstrated gate-tunable changes in transport properties, the full depletion of bulk carriers, as well as the successful realization of combined gate-tunable Josephson supercurrents and normal-state transport of Josephson junctions and Hall bar devices fabricated sideby-side [21,125].…”
Section: Quantum Transport In Bi 2 Te 3 Thin Filmsmentioning
confidence: 99%
“…(a) Reprinted and partly adapted with permission from [40], © 2018 American Physical Society. (b)-(c) Reprinted from[131]; and (d)-(f) from[121] with permission of AIP Publishing.…”
mentioning
confidence: 99%
“…However, it has been gradually realized that both these two planar magneto transport effects, namely, the positive LMC and PHE, are not sufficient transport signatures to guarantee the presence of CA in WSMs. Recently, it has been reported that similar planar transport behaviors can also arise through various extrinsic mechanisms [11,[15][16][17][18][19] and even appear in * ygyao@bit.edu.cn materials without any Weyl nodes [20][21][22][23][24][25][26][27][28][29][30][31][32]. In addition, Weyl nodes themselves do not always exhibit positive LMC.…”
Section: Introductionmentioning
confidence: 99%